2018
DOI: 10.1007/s12671-018-0905-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Stress, Affect, and Irritability Following Brief Use of a Mindfulness-based Smartphone App: A Randomized Controlled Trial

Abstract: Mindfulness training, which involves observing thoughts and feelings without judgment or reaction, has been shown to improve aspects of psychosocial well-being when delivered via in-person training programs such as mindfulness-based stress reduction (MBSR) and mindfulness-based cognitive therapy (MBCT). Less is known about the efficacy of digital training mediums, such as smartphone apps, which are rapidly rising in popularity. In this study, novice meditators were randomly allocated to an introductory mindful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
177
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 48 publications
10
177
2
2
Order By: Relevance
“…Given the evidence that workplace exposure to stressors is estimated to cost approximately $125 billion per year (Goh, Pfeffer, &Zenios, 2015), finding effective methods to reduce stress and burnout is critical to reducing healthcare costs and mortality rates for United States workers. Mindful meditation interventions using a mobile appoffer an efficient alternative to in-person interventions (Economides et al, 2018) and are effective at improving psychological health outcomes like burnout. The current research has important implications for busy individuals who are in positions with high burnout, such as teaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the evidence that workplace exposure to stressors is estimated to cost approximately $125 billion per year (Goh, Pfeffer, &Zenios, 2015), finding effective methods to reduce stress and burnout is critical to reducing healthcare costs and mortality rates for United States workers. Mindful meditation interventions using a mobile appoffer an efficient alternative to in-person interventions (Economides et al, 2018) and are effective at improving psychological health outcomes like burnout. The current research has important implications for busy individuals who are in positions with high burnout, such as teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, mindful meditation is considered an effective therapeutic approach. There are positive effects of mindfulness interventions on factors such as stress, affect, irritability, anxiety, and depression (Economides, Martman, Bell, & Sanderson, 2018;Ly et al, 2014;Spijkerman et al, 2016). It appears that engaging in thoughtful awareness of one's surroundings without judgment helps moderate strong emotions (Baer, 2003).…”
Section: The Benefits Of Mindful Meditationmentioning
confidence: 99%
“…Participants randomized to the mindfulness group were provided a 1-year subscription to Headspace (https://www.headspace.com/), a popular mindfulness meditation app that has over 20 million worldwide downloads [14] and which has been highly rated in content evaluations [42]. Participants randomized to the app group were instructed to complete the 10-minute version of levels 1, 2, and 3 of the Foundation series during their 12 minute break each day.…”
Section: Mindfulness Meditation Appmentioning
confidence: 99%
“…While mobile technology applied to health promotion has the potential to prevent disease and reduce health disparities, there is relatively little rigorous empirical research to accompany the growth of this health technology [13]. However, a recent spate of research indicates that app-delivered mindfulness meditation reduces self-reported stress, irritability [14], depression [15], burnout, and compassion fatigue [16], and attenuates the cortisol response to a psychosocial stress test compared to active control conditions [17]. App-based programming may prove particularly important for workforce populations with extreme time demands [16] and for more rural and blue-collar workforces, which have lower rates of access and engagement with workplace mindfulness programming [18], and which present unique challenges for workplace well-being (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the Headspace app was the highest-rated mindfulness app according to a structured app scoring system (Mani et al, 2015). Third, randomized control trials have demonstrated that 10-day mindfulness training through Headspace reduces depression, stress, and irritability and increases positive affect (Economides, Martman, Bell, & Sanderson, 2018;Howells, Ivtzan, & Eiroa-Orosa, 2016). Thus, previous research shows that brief use of Headspace has important therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%